Bilateral Congenital Corneal Opacities as an Early-Onset Ocular Feature of Kabuki Syndrome. Issue 9 (September 2019) - Lin, Po-An; Tseng, Sung-Huei; Lai, I-Wen; Huang, Yi-Hsun
Abstract : Purpose: Kabuki syndrome (KS) is a rare congenital disorder characterized by multiple systemic anomalies and unique facial characteristics. Here, we present the first case, to the best of our knowledge, of bilateral congenital corneal opacities as an early-onset ocular manifestation of KS associated with a KMT2D gene mutation. Methods: The proband is a girl. At birth, bilateral corneal opacities, short fifth fingers, patent ductus arteriosus, absence of the uvula, and an ectopic kidney on the right side were noted. Ophthalmic examinations revealed vascularized, nonhomogeneous opacities in both corneas; to prevent deprivation amblyopia, bilateral corneal transplantations were performed. Results: At 1 year and 10 months of age, she was referred by a general practitioner to our pediatric endocrinologist for failure to thrive. Genetic analysis at that age revealed the presence of a KMT2D gene mutation, and the patient was diagnosed with KS. Conclusions: The clinical diagnosis of KS is challenging because the most remarkable facial features are not evident until early childhood. In this case, bilateral congenital corneal opacities were identified as an early-onset ocular manifestation of KS. KS should be considered as a differential diagnosis in patients with bilateral congenital corneal opacities.